2023
DOI: 10.1186/s12916-023-02963-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional level of inflammation markers associates with short-term brain structural changes in first-episode schizophrenia

Abstract: Background Inflammation has been implicated in the pathology of schizophrenia and may cause neuronal cell death and dendrite loss. Neuroimaging studies have highlighted longitudinal brain structural changes in patients with schizophrenia, yet it is unclear whether this is related to inflammation. We aim to address this question, by relating brain structural changes with the transcriptional profile of inflammation markers in the early stage of schizophrenia. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…On the other hand, immuno-metabolic dysregulation is expected to primarily affect brain structure through inflammatory processes triggered by obesity ( 91 ) which have the capacity to exert widespread cortical effects ( 34 ). Our findings of regional variation in increases or decreases of MRI-derived measures of gray matter structure mediated by the immuno-metabolic pathway coincide with previous studies independently linking immune ( 68 , 92 ) and metabolic dysregulation ( 93 ) to macroscopic brain structure. This suggests that inflammatory processes capable of modulating brain structure have consequences for neuronal health that vary on a region-by-region basis.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, immuno-metabolic dysregulation is expected to primarily affect brain structure through inflammatory processes triggered by obesity ( 91 ) which have the capacity to exert widespread cortical effects ( 34 ). Our findings of regional variation in increases or decreases of MRI-derived measures of gray matter structure mediated by the immuno-metabolic pathway coincide with previous studies independently linking immune ( 68 , 92 ) and metabolic dysregulation ( 93 ) to macroscopic brain structure. This suggests that inflammatory processes capable of modulating brain structure have consequences for neuronal health that vary on a region-by-region basis.…”
Section: Resultssupporting
confidence: 90%
“…Increased peripheral monocytes may suggest activation of microglia in central nervous system (43). As a type of macrophage, activated microglia interferes with neuronal development and disrupts the function of neuronal circuits in the brain (44).For example, Cui et al (45) found that high transcript levels of monocyte genes across cortical regions were associated with cortical thinning in patients with psychosis by a high-resolution T1-weighted structural image, while cortical thickness could reflect neurodevelopmental status. Third, our study found that lymphocytes significantly decreased in patients but did not correlate with the total score of BPRS.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were prescribed antipsychotic medications without delay upon admission, which may affect inflammatory cytokine levels. However, the usage duration of all patients was less than two weeks and was not enough to exert the therapeutic effect [ 10 , 11 ]. Moreover, there is no observed correlation between CPZ and TNF-α level( p = 0.855), suggesting that the impact of antipsychotic medications on our findings was likely minimal.…”
Section: Discussionmentioning
confidence: 99%
“…The ethical approval number is 2022-15 Research. The inclusion criteria were as follows: (1) diagnosis of schizophrenia confirmed by two psychiatrists based on the Structured Clinical Interview for DSM-IV (SCID); (2) age 15–55 years old; (3) previous antipsychotic exposure did not exceed 2 weeks [ 10 , 11 ]; and (4) total disease duration ≤ 60 months. The exclusion criteria were the following: (1) other psychiatric disorders meeting DSM-IV Axis I diagnosis; (2) co-morbidity of acute, unstable, and/or significant untreated medical illnesses; (3) documented disease of the central nervous system (CNS); (4) history of chronic inflammation, autoimmune disorder, or severe allergy; (5) pregnancy or breastfeeding state; (6) dependence on alcohol or illicit drugs; (7) use of non-steroid anti-inflammatory drugs within the previous 4 weeks; and (8) no capacity to understand the study and provide written informed consent.…”
Section: Methodsmentioning
confidence: 99%